Transcription factors Sox8 and Sox10 perform non-equivalent roles during oligodendrocyte development despite functional redundancy. - Wegner, Michael; Stolt, Claus; et al. (Development, 2004)
Development of myelin-forming oligodendrocytes in the central nervous system is dependent on at least two members of the Sox family of high-mobility-group-containing transcription factors. Sox9 is involved in oligodendrocyte specification, whereas Sox10 is required for terminal differentiation. We show that oligodendrocytes in the spinal cord additionally express the highly related Sox8. In Sox8-deficient mice, oligodendrocyte development proceeded normally until birth. However, terminal differentiation of oligodendrocytes was transiently delayed at early postnatal times. Sox8-deficient mice thus exhibited a similar, but less severe phenotype than did Sox10-deficient mice. Terminal oligodendrocyte differentiation was dramatically delayed in Sox8-deficient mice with only a single functional Sox10 allele hinting at redundancy between both Sox proteins. This redundancy was also evident from the fact that Sox8 bound to naturally occurring Sox10 response elements, was able to form DNA-dependent heterodimers with Sox10 and activated Sox10-specific oligodendrocytic target genes in a manner similar to Sox10. However, Sox8 expression levels were significantly lower than those for Sox10. Resulting differences in protein amounts might be a main reason for the weaker impact of Sox8 on oligodendrocyte development and for unidirectional compensation of the Sox8 loss by Sox10.
UnivIS-Import:2015-03-09:Pub.2004.med.IB.LPCIPDBI.transc
Keywords: Gene dosage; High-mobility-group; Oligodendrocyte; Redundancy; Sox10; Sry